ANALISIS HUBUNGAN ANTARA HARGA MINYAK, PASAR SAHAM, DAN NILAI TUKAR DI INDONESIA - Nadia Kurnianti; Idris Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
The aim of this research is to analyze the relationship of causality between oil prices, stocks market, and exchange rates in Indonesia using VAR model. The data used in this study is time series data from January 2014 until December 2018 that was obtained from the relevant institutions. The variables use are oil prices (X1), stocks market (X2), and exchange rates (X3). The method used in this study is Vector Auto Reggression (VAR). The finding has shown that there are no causality relationship between the oil prices, stock markets, and exchanger rates. The finding also shown that there is only directional relationship between exchange rates with stocks market.